Medi Karaketristik Morfometrik Dan Meristik Ikan Gabus (Channa striata) Pada Beberapa Tipe Perairan Yang Berbeda di Pulau Bangka - Medi Rismanto; Andi Gustomi; Sudirman Adibrata (Akuatik: Jurnal Sumberdaya Perairan, 2023)
This study aims to analyze the morphometric and meristic characteristics of snakehead fish (Channa striata) for different water qualities. Sampling was carried out in July-October 2019 at Nyelanding Air Gegas Hot Spring, Lubuk Bakong Tua Tunu Pangkalpinang River, and Under the Simpur Pemali Dam. Determination of the sampling point is done by purposive sampling method. Based on the morphometric analysis of snakehead fish (Channa striata) from three different research locations, namely having a total length of 15-27 cm in Nyelanding Hot Springs; total length of 21.5-24 cm in the Lubuk Bakong River; total length of 20-26 cm under the Simpur Dam. The results of meristic analysis of snakehead fish in three waters, namely having dorsal fin radii D.II.7-D.III.14 Nyelanding Hot Water, D.II.11-D.II.15 Lubuk Bakong River, D.II.9- D.IV.15 Under the Simpur Dam. Based on its morphometric characteristics, it is divided into 23 parts, while meristic is divided into 9 parts. The water quality parameters of snakehead fish in the three waters ranged from temperature 29-38 â„ƒ, degree of acidity 5-6.5, brightness 0.25-0.33 m, depth 1.10-2.10 m, current speed 0.02- 0.03 m/s, Total Suspended Solids 4-9 mg/l.